Transformasi Fungsi Pembatalan Perkawinan Dalam Hukum Keluarga Islam Kontemporer di Indonesia - Alfiyah Faizatul Arif (MASADIR: Jurnal Hukum Islam, 2026)
In Islamic law, the dissolution of marriage is recognized through several mechanisms, namely talaq, khulu', and fasakh. Among these mechanisms, fasakh is closely related to the annulment of marriage in contemporary Islamic family law because both are based on specific legal grounds for ending the marital relationship. As society and the family law system develop, the function of annulment of marriage has undergone a transformation. Annulment of marriage is no longer understood solely as a corrective mechanism for marriages that do not meet legal requirements, but also as an instrument to respond to various deviant marital practices, such as falsification or concealment of identity, concealment of marital status, and violations of marital law provisions. This article aims to analyze the transformation of the function of annulment of marriage from the perspective of contemporary Islamic family law in Indonesia. This research is a normative legal research with a conceptual approach and a sociological perspective of Islamic law based on library studies. Data were obtained through a review of Islamic family law literature, legislation, the Compilation of Islamic Law, and relevant academic literature. The research findings indicate that marriage annulment has undergone a functional transformation from a mechanism for resolving marriages based on specific legal grounds to an instrument for protecting rights, providing legal certainty, enforcing orderly marriage administration, and preventing various deviant marital practices. This transformation demonstrates that Islamic family law is dynamic and responsive to social change without neglecting the basic principles of sharia.